2022
DOI: 10.3168/jds.2021-21025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid-producing bacteria as direct-fed microbials on the ruminal microbiome

Abstract: The objective of this study was to evaluate ruminal microbiome changes associated with feeding Lactobacillus plantarum GB-LP1 as direct-fed microbials (DFM) in high-producing dairy cow diets. A dual-flow continuous culture system was used in a replicated 4 × 4 Latin square design. A basal diet was formulated to meet the requirements of a cow producing 45 kg of milk per day (16% crude protein and 28% starch). There were 4 experimental treatments: the basal diet without any DFM (CTRL); a mixture of Lactobacillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 63 publications
(97 reference statements)
3
6
2
Order By: Relevance
“…Abundance of phyla in the liquid fraction was dominated by Bacteroidetes (46.2% of sequences on average), whereas Firmicutes, Proteobacteria, Spirochaetes, Patescibacteria, and Fibrobacteres accounted on average for 25.8%, 12.2%, 8.2%, 1.3%, and 1.1%, respectively. Similar values of phylum relative abundances have been reported by Dai et al (2019) and Monteiro et al (2022) for samples collected from continuous-culture fermentors. We did not find any effect of Cho or NDF × Cho in the solid fraction; however, relative abundance of Firmicutes was greater for the 40% NDF diet, and conversely, Proteobacteria, Spirochaetes, and Patescibacteria were less abundant with the 40% NDF diet.…”
Section: Resultssupporting
confidence: 85%
“…Abundance of phyla in the liquid fraction was dominated by Bacteroidetes (46.2% of sequences on average), whereas Firmicutes, Proteobacteria, Spirochaetes, Patescibacteria, and Fibrobacteres accounted on average for 25.8%, 12.2%, 8.2%, 1.3%, and 1.1%, respectively. Similar values of phylum relative abundances have been reported by Dai et al (2019) and Monteiro et al (2022) for samples collected from continuous-culture fermentors. We did not find any effect of Cho or NDF × Cho in the solid fraction; however, relative abundance of Firmicutes was greater for the 40% NDF diet, and conversely, Proteobacteria, Spirochaetes, and Patescibacteria were less abundant with the 40% NDF diet.…”
Section: Resultssupporting
confidence: 85%
“…P-treated silage decreased the relative abundance of Firmicutes in the rumen fluid. Similar results were reported by Monteiro et al [27], who fed high-producing dairy cows with Lentilactobacillus plantarum directly. The diet has a great influence on the rumen microbiota.…”
Section: Resultssupporting
confidence: 90%
“…However, addition of microbial additives and enzymes (ADD) tended to decrease the relative abundance of Firmicutes in the solid fraction ( Table 2 ). Lower relative abundance of Firmicutes was reported by Monteiro et al (2022) for bacteria in the liquid fraction as a result of adding either Lactobacillus plantarum or a blend of Lactobacillus acidophilus and Propionibacterium freudenreichii to corn silage-based diets in continuous culture. Conversely, greater relative abundance of Firmicutes in ruminal fluid has been reported by Plaizier et al (2017) in cows with subacute ruminal acidosis resulting from a reduction of dietary NDF concentration, suggesting a positive association between Firmicutes relative abundance and ruminal acidity.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, in the liquid fraction we found that Prevotellaceae (20.9%), Succinivibrionaceae (20.0%), Lachnospiraceae (17.8%), Selenomonaceae (4.1%), and Spirochaetaceae (3.60%), were the most abundant families. Previous studies have already reported Prevotellaceae , Lachnospiraceae , Succinivibrionaceae , and Spirochaetaceae within the most abundant families in both solid and liquid fractions of ruminal cultures ( Arce-Cordero et al, 2022a ; Monteiro et al, 2022 ) and ruminal samples ( Söllinger et al, 2018 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation